Rehabilitating Valley Floors to a Stage 0 Condition: A Synthesis of Opening Outcomes - Flitcroft, Rebecca L.; Brignon, William R.; Staab, Brian; Bellmore, J. Ryan; Burnett, Jonathan; Burns, Paul; Cluer, Brian; Giannico, Guillermo; Helstab, Joseph M.; Jennings, Jeremy; Mayes, Christopher; Mazzacano, Celeste; et al. (Frontiers in Environmental Science, 2022)
Degraded floodplains and valley floors are restored with the goal of enhancing habitat for native fish and aquatic-riparian biota and the protection or improvement of water quality. Recent years have seen a shift toward “process-based restoration” that is intended to reestablish compromised ecogeomorphic processes resulting from site- or watershed-scale degradation. One form of process-based restoration has developed in the Pacific Northwest, USA, that is intended to reconnect rivers to their floodplains by slowing down flows of sediment, water, and nutrients to encourage lateral and vertical connectivity at base flows, facilitating development of dynamic, self-forming, and self-sustaining river-wetland corridors. Synergies between applied practices and the theoretical work of Cluer and Thorne in 2014 have led this form of restoration to be referred to regionally as restoration to a Stage 0 condition. This approach to rehabilitation is valley scale, rendering traditional monitoring strategies that target single-thread channels inadequate to capture pre- and post-project site conditions, thus motivating the development of novel monitoring approaches. We present a specific definition of this new type of rehabilitation that was developed in collaborative workshops with practitioners of the approach. Further, we present an initial synthesis of results from monitoring activities that provide a foundation for understanding the effects of this approach of river rehabilitation on substrate composition, depth to groundwater, water temperature, macroinvertebrate richness and abundance, secondary macroinvertebrate production, vegetation conditions, wood loading and configuration, water inundation, flow velocity, modeled juvenile salmonid habitat, and aquatic biodiversity.